The development of Calvin's understanding of the imago dei in the Institutes of the Christian Religion from 1536 to 1559 - Shih, Shu-Ying (2004)
The tension that exists in Calvin's theology between the imago dei and its state of deformity has been an issue of particular importance since the beginning of the twentieth century. This thesis aims at defining and examining the significance and legitimacy of the term "imago dei" in Calvin's Institutes of the Christian Religion. Part I presents a detailed chronological examination of all five editions of the Institutes - i.e. from 1536, 1539, 1543, 1550 and 1559 - focusing in particular on Calvin's understanding of the imago dei and its deformed state. Part II will then present a thematic investigation, picking up the major aspects of Calvin's work on the imago dei and following their development in the Institutes. A systematic reconstruction of Calvin's understanding of the imago dei will then be provided in Part III.
Keywords: Hochschulschrift; Gottebenbildlichkeit; Calvin, Jean / Christianae religionis institutio